Preparation method, product and application of high-thermal-conductivity nanoscale phase change microcapsule

By using high-thermal nanoscale phase-transformation microcapsules formed by hydrophobizing and epoxy resin wrapped in phase-transformation materials in the development of deep-water oil and gas fields, the problems of excessive cement hydration heat and low thermal conductivity of phase-transformation microcapsules are solved, and the effect of reducing cement hydration heat and improving the compressive strength of cement stone is achieved.

CN119707353AActive Publication Date: 2025-03-28TIANJIN UNIV

Patent Information

Application Number
CN202411948223.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

In the development of existing deep-water oil and gas fields, excessive cement hydration heat leads to blowout accidents, and the phase-change microcapsules have low thermal conductivity and mechanical properties that have a great impact.

Method used

The highly thermally conductive nanomaterial is hydrophobized by silane coupling agent, combined with epoxy resin to wrap the phase change material, and the high thermal conductivity nanoscale phase change microcapsules are formed through emulsification to improve their dispersion and thermal conductivity in cement.

Benefits of technology

It effectively reduces the hydration heat of cement, improves the compressive strength of cement stone, and avoids leakage of phase change materials and the negative impact of the mechanical properties of cement stone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707353A_ABST
    Figure CN119707353A_ABST
Patent Text Reader

Abstract

The invention relates to the field of concrete and deepwater oil-gas field development and well cementation, in particular to a preparation method, a product and application of a high-thermal-conductivity nanoscale phase change microcapsule. The preparation method comprises the following steps: carrying out hydrophobization treatment on a high-thermal-conductivity nano-material by adopting a silane coupling agent to obtain a hydrophobized high-thermal-conductivity nano-material; uniformly mixing a phase-change material, epoxy resin and a curing agent, then adding the hydrophobic high-thermal-conductivity nano material, and uniformly mixing to obtain an oil-phase mixture; dissolving a cationic emulsifier and a nonionic emulsifier in water to obtain an aqueous solution; and adding the oil-phase mixture into an aqueous solution under a stirring condition, reacting the obtained emulsion at a certain temperature, and then centrifuging the obtained solid and freeze-drying the solid to obtain the high-thermal-conductivity nanoscale phase change microcapsule. The high-thermal-conductivity nanoscale phase change microcapsule has a heat absorption function, can reduce hydration heat release of cement, has no negative influence on early compressive strength of set cement, and overcomes the defects of low-hydration-heat cement for deepwater well cementation at present.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of concrete and deepwater oil and gas field development cementing, and in particular to a preparation method, product and application of high thermal conductivity nano-scale phase change microcapsules. Background Art

[0002] Deepwater areas are rich in oil and gas resources and have significant exploration prospects. Low temperature and natural gas hydrate (NGH) decomposition are two major challenges in deepwater oil and gas resource exploration. The delayed hydration of cement slurry in a low-temperature environment leads to slow development of the mechanical properties of cement stone, making it easy for fluids such as oil, gas, and water in the formation to invade the cement sheath and cause blowout accidents. Secondly, the hydration of cement slurry releases a large amount of heat, causing natural gas hydrates to decompose endothermically, generating a large amount of gas that enters the cement slurry under pressure, resulting in continuous high pressure in the cement sheath, cracks, and affecting the quality of cementing.

[0003] Recent studies have shown that adding phase change materials (PCM) to cement can effectively reduce the hydration heat of cement. However, PCM has low density and poor compatibility with cement components, making it unsuitable for direct use in cement. It is usually encapsulated in a shell to form phase change microcapsules. At present, the shell materials of microcapsules are mainly organic polymers (formaldehyde resin, melamine resin, phenolic resin, etc.) and inorganic materials (calcium carbonate, silica, titanium dioxide, etc.). Inorganic materials have better compatibility with cement slurry and good thermal conductivity. However, the encapsulation of inorganic shell materials is poor, the particle size of the synthesized microcapsules is large, and the phase change enthalpy is low. Compared with inorganic shell materials, organic polymers have better encapsulation, chemical stability and mechanical strength. However, the thermal conductivity of organic polymer shell phase change microcapsules is low, resulting in a decrease in the heat absorption efficiency of the microcapsules. Secondly, the research results show that whether it is an organic shell material or an inorganic shell material, the addition of phase change microcapsules will inevitably have a negative impact on the mechanical properties of cement paste. Summary of the invention

[0004] Based on the above content, the present invention provides a preparation method, product and application of high thermal conductivity nano-scale phase change microcapsules. The high thermal conductivity nano-scale phase change microcapsules of the present invention have high thermal conductivity and phase change enthalpy, can reduce the heat of cement hydration, and have no negative impact on the strength of cement paste, solving the shortcomings of current phase change microcapsules for deepwater cementing.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a method for preparing a high thermal conductivity nanoscale phase change microcapsule, comprising the following steps:

[0007] A silane coupling agent is used to perform hydrophobic treatment on the high thermal conductivity nanomaterial to obtain a hydrophobic high thermal conductivity nanomaterial;

[0008] Mixing a phase change material, an epoxy resin and a curing agent to obtain an oil phase solution; adding a hydrophobic high thermal conductivity nanomaterial to the oil phase solution and mixing to obtain an oil phase mixture;

[0009] dissolving a cationic emulsifier and a nonionic emulsifier in water to obtain an aqueous solution;

[0010] adding the oil phase mixture to the aqueous solution under stirring conditions to obtain an emulsion;

[0011] The emulsion is reacted and then centrifuged to obtain a solid; the solid is freeze-dried to obtain the high thermal conductivity nano-scale phase change microcapsule.

[0012] The second technical solution of the present invention is a high thermal conductivity nanoscale phase change microcapsule prepared according to the preparation method.

[0013] The third technical solution of the present invention is the application of the high thermal conductivity nano-scale phase change microcapsules in cement.

[0014] The present invention discloses the following technical effects:

[0015] The present invention can improve the dispersibility of nanomaterials in the oil phase by hydrophobic modification of high thermal conductivity nanomaterials, making it easier to form a thermal conduction path, thereby improving the thermal conductivity of the microcapsule. Secondly, using epoxy resin as a shell, the leakage of the phase change material during the phase change process can be avoided by wrapping the phase change material. In addition, the hydroxyl groups on the surface of the epoxy resin can improve the dispersibility of cement slurry particles, thereby promoting more uniform hydration of cement slurry, producing a more compact cement stone structure, and promoting the strength development of cement stone. Secondly, compared with micron-level phase change microcapsules, nano-level phase change microcapsules can be better dispersed in cement slurry, avoiding the formation of larger stress defects in cement stone. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 SEM images and TEM images of the high thermal conductivity nanoscale phase change microcapsules prepared in Example 1, Example 2 and Example 3; wherein (a) is the SEM image of Example 1, (b) is the SEM image of Example 2, (c) is the SEM image of Example 3, and (d) is the TEM image of Example 2.

[0018] Figure 2Phase change enthalpy diagram of the high thermal conductivity nanoscale phase change microcapsules prepared in Example 1, Example 4 and Example 5.

[0019] Figure 3 Graph showing thermal conductivity of high thermal conductivity nanoscale phase change microcapsules prepared in Example 1, Example 2 and Example 3.

[0020] Figure 4 The hydration heat test diagram of oil well cement slurry added with different amounts of high thermal conductivity nano-scale phase change microcapsules prepared in Example 1.

[0021] Figure 5 The compressive strength of oil well cement paste mixed with different amounts of high thermal conductivity nano-scale phase change microcapsules prepared in Example 1 after 1 day, 2 days and 3 days. DETAILED DESCRIPTION

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0027] Phase change materials refer to substances that change their state and provide latent heat without changing the temperature. They have the advantages of large melting latent heat and large heat storage density. They can usually be divided into organic phase change materials and inorganic phase change materials. Among them, organic phase change materials are the most popular type of phase change materials because of their good chemical stability and high thermal melting. They absorb and release heat through their own melting and solidification processes, thereby realizing energy storage and temperature control. They are relatively easy to use and are widely used in business. For example, in the field of construction, phase change materials can be used for enclosure structures, roofs, floors, domestic hot water tanks and energy equipment. In the food industry, they can be used in refrigerators, food packaging, and transportation systems. However, organic phase change materials will change from solid phase to liquid phase during the phase change process, showing inherent defects such as low thermal conductivity and leakage, which will reduce the heat storage efficiency of the material and hinder its practical application. Therefore, for most applications, solid-liquid organic phase change materials need to be sealed by encapsulation or shape stabilization methods.

[0028] Microcapsules are a type of micro-packaging technology that encapsulates tiny solid, liquid or gaseous materials in a shell of a natural or synthetic polymer matrix to protect unstable or sensitive functional materials. Therefore, microencapsulation of phase change materials can effectively exert the energy storage characteristics of phase change materials. The main advantages of microcapsule phase change materials over phase change materials are: ① a larger heat transfer area; ② reducing the reactivity of PCM to the external environment, making it easier to control the volume change of phase change materials. The present invention intends to prepare high thermal conductivity nano-scale phase change microcapsules, which have a heat absorption function and can reduce the heat of cement hydration while having no negative impact on the compressive strength of cement paste. Phase change microcapsules are formed by encapsulating phase change materials with epoxy resin, and hydrophobic high thermal conductivity nanomaterials are added to improve the heat absorption efficiency of microcapsules. The heat released by cement hydration is absorbed by the phase change material to reduce the heat of cement hydration; the hydroxyl groups on the surface of epoxy resin are used to improve the dispersibility of cement slurry particles, thereby improving the compressive strength of cement paste.

[0029] The first aspect of the present invention provides a method for preparing a high thermal conductivity nanoscale phase change microcapsule, comprising the following steps:

[0030] A silane coupling agent is used to perform hydrophobic treatment on the high thermal conductivity nanomaterial to obtain a hydrophobic high thermal conductivity nanomaterial;

[0031] Mixing a phase change material, an epoxy resin and a curing agent to obtain an oil phase solution; adding a hydrophobic high thermal conductivity nanomaterial to the oil phase solution and mixing to obtain an oil phase mixture;

[0032] dissolving a cationic emulsifier and a nonionic emulsifier in water to obtain an aqueous solution;

[0033] Adding the oil phase mixture into the aqueous solution and stirring at high speed for a certain period of time to obtain a stable emulsion;

[0034] The emulsion is reacted and then centrifuged to obtain a solid; the solid is freeze-dried to obtain the high thermal conductivity nano-scale phase change microcapsule.

[0035] In some embodiments of the present invention, the silane coupling agent is vinyltriethoxysilane, vinyltrimethoxysilane or octadecyltrimethoxysilane; the high thermal conductivity nanomaterial is boron nitride; the mass ratio of the silane coupling agent to the high thermal conductivity nanomaterial is (1-2):1; the hydrophobic treatment is specifically adding the high thermal conductivity nanomaterial to the silane coupling agent solution at 60-80°C for reaction for 4-6h; the solvent of the silane coupling agent solution is acetic acid aqueous solution; the pH of the silane coupling agent solution is 2-6; the concentration of the silane coupling agent in the silane coupling agent solution is 0.02-0.04g / mL.

[0036] The hydrophobic treatment also includes a step of ultrasonic dispersion before the hydrophobic treatment; after the hydrophobic treatment, the solid matter is centrifugally separated and washed, dried and ground; the drying temperature is 90°C.

[0037] In some embodiments of the present invention, the phase change material is methyl stearate or ethyl stearate; the epoxy resin is epoxy resin E-51, epoxy resin CYDH-3000 or epoxy resin NP170; the curing agent is 4,4′-diaminodicyclohexylmethane (DDCM) or 3,3′-diethyl-4,4′-diaminodiphenylmethane (DEDDM); the mass ratio of the phase change material to the epoxy resin is (2-3):1; the mass ratio of the epoxy resin to the curing agent is 1:0.3. The phase change material and the epoxy resin have a great influence on the phase change enthalpy of the phase change microcapsules. If the amount of epoxy resin is too large, the phase change enthalpy of the microcapsules will decrease. If the amount of epoxy resin is too small, the phase change material cannot be completely wrapped, resulting in leakage. Therefore, the present invention preferably limits the amount of phase change material and epoxy resin to the above-mentioned ratio range.

[0038] In some embodiments of the present invention, the mass ratio of the oil phase solution to the hydrophobized high thermal conductivity nanomaterial is (8.5-10):(0.09-0.3).

[0039] When the hydrophobized high thermal conductive nanomaterial is added to the oil phase solution and mixed to prepare the oil phase mixture, a cell crusher with a power of 800 W is used to ultrasonically mix the oil phase solution and the hydrophobized high thermal conductive nanomaterial for 10-20 minutes.

[0040] In some embodiments of the present invention, the cationic emulsifier is dodecyltrimethylammonium bromide or dodecyltrimethylammonium chloride; the nonionic emulsifier is dodecylphenol polyoxyethylene ether (OP-10), sorbitan fatty acid ester (Span-80) or polysorbate-20 (Tween-20); the concentration of the cationic emulsifier in the aqueous solution is 0.13-0.15 g / mL; the concentration of the nonionic emulsifier in the aqueous solution is 0.4-0.45 g / mL.

[0041] In some embodiments of the present invention, the mass volume ratio of the oil phase mixture to the aqueous solution is (9-11) g:100 mL; when preparing the stable emulsion, the stirring conditions are: stirring at a speed of 8000-12000 r / min for 8-10 min.

[0042] In the present invention, the particle size of the microcapsules is affected by the amount of emulsifier used and the stirring speed. The present invention limits the emulsifier concentration to: the concentration of the cationic emulsifier in the aqueous solution is 0.13-0.15 g / mL; the concentration of the nonionic emulsifier in the aqueous solution is 0.4-0.45 g / mL; the stirring speed and time are limited to: stirring at a speed of 8000-12000 r / min for 8-10 min; the phase change microcapsules prepared within the above parameter range are nanometer-level; when the emulsifier concentration and stirring conditions exceed the above-mentioned parameter range, the particle size of the prepared microcapsules will be affected, and the preparation of nanometer-level phase change microcapsules cannot be achieved.

[0043] In some embodiments of the present invention, the reaction temperature is 80-100° C. and the reaction time is 4-6 h.

[0044] The present invention does not impose any particular limitation on freeze-drying parameters such as pressure, temperature, and time, and the freeze-drying parameters commonly used in the art may be used.

[0045] After the emulsion reaction is completed, the centrifugal speed is 8000-12000r / min and the time is 8-10min.

[0046] The second aspect of the present invention provides a high thermal conductivity nanoscale phase change microcapsule prepared according to the preparation method.

[0047] The third aspect of the present invention provides the use of the high thermal conductivity nano-scale phase change microcapsules in cement.

[0048] In some embodiments of the present invention, the amount of the high thermal conductivity nano-scale phase change microcapsules added to cement is 1-5% of the mass of the cement.

[0049] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0050] The cement used in the embodiment of the present invention is Jiahua G-grade oil well cement; other types of oil well cement can also be used in the present invention.

[0051] The mass unit in each embodiment of the present invention may be gram or kilogram or other mass units.

[0052] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0053] Example 1

[0054] The preparation method of high thermal conductivity nano-scale phase change microcapsules (abbreviated as: phase change microcapsules) comprises the following steps:

[0055] (1) Add acetic acid to 100 mL of water to adjust the pH to 4, then add 0.02 g / mL of vinyl triethoxysilane and stir thoroughly to dissolve. Add 1 g of boron nitride to the above silane coupling agent solution, add it to a flask after ultrasonic dispersion, and react at 60° C. for 4 h. After the reaction is completed, separate the solid matter by centrifugation, wash it with deionized water, dry it, and grind it to obtain hydrophobic boron nitride (there is no requirement for the particle size of the grinding, just grind it into fine powder).

[0056] (2) Weigh 6 g of methyl stearate, melt it at 60°C, add 3 g of epoxy resin E51, stir and mix thoroughly, add 0.9 g of curing agent DDCM, stir and mix again to form an oil phase solution. Add 0.099 g of hydrophobized boron nitride, and ultrasonicate at 800 W for 10 min to obtain an oil phase mixture.

[0057] (3) Add 0.14 g of dodecyltrimethylammonium bromide and 0.44 g of OP-10 to 100 mL of water, stir and fully dissolve to obtain a uniform aqueous solution, and place the aqueous solution in a 60° C. water bath and heat at a constant temperature.

[0058] (4) At a stirring speed of 12000 r / min, 10.197 g of the oil phase mixture was added to 100 mL of the aqueous solution, and then stirred for 10 min to obtain a uniform emulsion.

[0059] (5) The uniform emulsion was placed in a 90° C. water bath for reaction for 6 h. After the reaction was completed, the solid portion was obtained by centrifugation and freeze-dried to obtain powdered phase change microcapsules.

[0060] Example 2

[0061] The preparation method of high thermal conductivity nano-scale phase change microcapsules, the steps are as follows:

[0062] (1) Add acetic acid to 100 mL of water to adjust the pH to 3, then add 0.03 g / mL of vinyl triethoxysilane and stir to dissolve. Add 2 g of boron nitride to the above silane coupling agent solution, add it to a flask after ultrasonic dispersion, and react at 60° C. for 4 h. After the reaction is completed, separate the solid matter by centrifugation, wash with deionized water, dry it, and grind it to obtain hydrophobic boron nitride.

[0063] (2) Weigh 6 g of ethyl stearate, melt it at 60°C, add 3 g of epoxy resin CYDH-3000, stir and mix thoroughly, add 0.9 g of curing agent DDCM, stir and mix again to form an oil phase solution. Add 0.198 g of hydrophobized boron nitride, and ultrasonicate at 800 W for 10 min to obtain an oil phase mixture.

[0064] (3) Add 0.14 g of dodecyltrimethylammonium bromide and 0.44 g of OP-10 to 100 mL of water, stir and fully dissolve to obtain a uniform aqueous solution, and place the aqueous solution in a 60° C. water bath and heat at a constant temperature.

[0065] (4) At a stirring speed of 8000 r / min, 10.098 g of the oil phase mixture was added to 100 mL of the aqueous solution, and then the stirring was continued for 10 min to obtain a uniform emulsion.

[0066] (5) The uniform emulsion was placed in a 90° C. water bath for reaction for 6 h. After the reaction was completed, the solid portion was obtained by centrifugation and freeze-dried to obtain powdered phase change microcapsules.

[0067] Example 3

[0068] The preparation method of high thermal conductivity nano-scale phase change microcapsules, the steps are as follows:

[0069] (1) Add acetic acid to 100 mL of water to adjust the pH to 4, then add 0.02 g / mL of vinyl triethoxysilane and stir to dissolve. Add 1 g of boron nitride to the above silane coupling agent solution, add it to a flask after ultrasonic dispersion, and react at 60° C. for 4 h. After the reaction is completed, separate the solid matter by centrifugation, wash with deionized water, dry it, and grind it to obtain hydrophobic boron nitride.

[0070] (2) Weigh 6 g of ethyl stearate, melt it at 60°C, add 3 g of epoxy resin CYDH-3000, stir and mix thoroughly, add 0.9 g of curing agent DDCM, stir and mix again to form an oil phase solution. Add 0.297 g of hydrophobic modified boron nitride, and ultrasonicate at 800 W for 10 min to obtain an oil phase mixture.

[0071] (3) Add 0.15 g of dodecyltrimethylammonium bromide and 0.43 g of OP-10 to 100 mL of water, stir and fully dissolve to obtain a uniform aqueous solution, and place the aqueous solution in a water bath at 60° C. and heat at a constant temperature.

[0072] (4) At a stirring speed of 8000 r / min, 9.197 g of the oil phase mixture was added to 100 mL of the aqueous solution, and then stirred for 10 min to obtain a uniform emulsion.

[0073] (5) The uniform emulsion was placed in a 100° C. water bath for reaction for 6 h. After the reaction was completed, the solid part was obtained by centrifugation, and then freeze-dried to obtain powdered phase change microcapsules.

[0074] Example 4

[0075] The preparation method of high thermal conductivity nano-scale phase change microcapsules, the steps are as follows:

[0076] (1) Add acetic acid to 100 mL of water to adjust the pH to 4, then add 0.02 g / mL of vinyl triethoxysilane and stir to dissolve. Add 2 g of boron nitride to the above silane coupling agent solution, add it to a flask after ultrasonic dispersion, and react at 60° C. for 6 h. After the reaction is completed, separate the solid matter by centrifugation, wash with deionized water, dry it, and grind it to obtain hydrophobic boron nitride.

[0077] (2) Weigh 6 g of methyl stearate, melt it at 60°C, add 3 g of epoxy resin NP170, stir and mix thoroughly, add 0.9 g of curing agent DDCM, stir and mix again to form an oil phase solution. Add 0.297 g of hydrophobic modified boron nitride, and ultrasonicate at 800 W for 10 min to obtain an oil phase mixture.

[0078] (3) Add 0.15 g of dodecyltrimethylammonium bromide and 0.43 g of OP-10 to 100 mL of water, stir and fully dissolve to obtain a uniform aqueous solution, and place the aqueous solution in a water bath at 60° C. and heat at a constant temperature.

[0079] (4) At a stirring speed of 12000 r / min, 10.197 g of the oil phase mixture was added to 100 mL of the aqueous solution, and then stirred for 10 min to obtain a uniform emulsion.

[0080] (5) The uniform emulsion was placed in a water bath at 80° C. for reaction for 4 h. After the reaction was completed, the solid portion was obtained by centrifugation and freeze-dried to obtain powdered phase change microcapsules.

[0081] Example 5

[0082] The preparation method of high thermal conductivity nano-scale phase change microcapsules, the steps are as follows:

[0083] (1) Add acetic acid to 100 mL of water to adjust the pH to 6, then add 0.02 g / mL of vinyl triethoxysilane and stir to dissolve. Add 2 g of boron nitride to the above silane coupling agent solution, add it to a flask after ultrasonic dispersion, and react at 60° C. for 6 h. After the reaction is completed, separate the solid matter by centrifugation, wash with deionized water, dry it, and grind it to obtain hydrophobic boron nitride.

[0084] (2) Weigh 6 g of methyl stearate, melt it at 60°C, add 2 g of epoxy resin E51, stir and mix thoroughly, add 0.6 g of curing agent DDCM, stir and mix again to form an oil phase solution. Add 0.297 g of hydrophobic modified boron nitride, and ultrasonicate at 800 W for 10 min to obtain an oil phase mixture.

[0085] (3) Add 0.15 g of dodecyltrimethylammonium bromide and 0.43 g of OP-10 to 100 mL of water, stir and fully dissolve to obtain a uniform aqueous solution, and place the aqueous solution in a water bath at 60° C. and heat at a constant temperature.

[0086] (4) At a stirring speed of 10000 r / min, 9.897 g of the oil phase mixture was added to 100 mL of the aqueous solution, and then the stirring was continued for 10 min to obtain a uniform emulsion.

[0087] (5) The uniform emulsion was placed in a 90° C. water bath for reaction for 4 h. After the reaction was completed, the solid portion was obtained by centrifugation and freeze-dried to obtain powdered phase change microcapsules.

[0088] In order to detect whether the encapsulation process of the phase change material is successful, the microscopic morphology of the high thermal conductivity nano-scale phase change microcapsules (hereinafter referred to as phase change microcapsules) prepared in Example 1, Example 2, and Example 3 was observed using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). Phase change material, epoxy resin and curing agent form a uniform oil phase solution. When it is added to an aqueous solution, the lipophilic group in the emulsifier faces the oil phase part, and the hydrophilic group faces the aqueous solution. Under the action of mechanical stirring, the oil phase is evenly dispersed in the aqueous solution to form a stable emulsion. At high temperatures, the amine group in the curing agent and the epoxy group produce a ring-opening reaction, and finally form a cross-linked network structure. The cured epoxy resin is incompatible with the phase change material, gradually precipitates out from the oil phase solution, and under the action of stirring and centrifuging, it is wrapped around the phase change material to form an encapsulation. The modified boron nitride is hydrophobicized and is basically insoluble in aqueous solution. It can be stably present in the oil phase solution, and as the epoxy resin is cured, it is interspersed in the epoxy resin and the phase change material. Example 1, Example 2 and Example 3 show the appearance of phase change microcapsules with different contents of hydrophobized boron nitride added. Figure 1(SEM) shows that the microcapsules have a consistent spherical structure, and the surface shows different degrees of particle protrusions, which should be the hydrophobic boron nitride interspersed in the oil phase. As the amount of hydrophobic boron nitride added increases, the number of surface particles also increases significantly. In addition, it can be seen that the hydrophobic boron nitride is embedded in the shell material instead of simply adhering to the surface. This shows that the hydrophobic boron nitride has good compatibility with epoxy resin and can be well embedded in the epoxy matrix. Figure 1 It can be seen from TEM that the microcapsules have a distinct core-shell structure, and the hydrophobic boron nitride can be well dispersed and embedded in the core and shell of the microcapsules. The above results prove the successful synthesis of phase change microcapsules. Figure 1 It can also be seen that the particle size distribution of the high thermal conductivity nanoscale phase change microcapsules prepared in Examples 1, 2 and 3 of the present invention is nanoscale.

[0089] The phase change enthalpy changes of Example 1, Example 4 and Example 5 were tested by differential scanning calorimetry (DSC). Figure 2 As shown. The phase change temperatures of the microcapsules prepared in Example 1, Example 4 and Example 5 are 42.8°C, 43.6°C, and 3.2°C, respectively, and the phase change enthalpies are 179.9 J / g, 179.4 J / g and 174.4 J / g, respectively. The phase change enthalpies of Example 1 and Example 4 are not much different. On the contrary, the phase change enthalpy of Example 5 is significantly reduced. This is because the less epoxy resin cannot completely wrap the phase change material. During the subsequent cleaning process, the phase change material is lost, resulting in a decrease in the phase change enthalpy of the phase change microcapsules. The thermal conductivity of the microcapsules prepared in Example 1, Example 2 and Example 3 was tested by a thermal conductivity meter, as shown Figure 3 As shown in the figure, it can be seen that with the increase of the amount of hydrophobic boron nitride added, the thermal conductivity of the microcapsule increases significantly, indicating that the hydrophobic boron nitride plays a good role in thermal conductivity in the microcapsule.

[0090] The phase change microcapsules prepared in Example 1 were added to the cement system at 1%, 3% and 5% of the mass of Jiahua G-grade oil well cement. The preparation method of the cement slurry referred to the standard GB / T.19139-2012 "Test Methods for Oil Well Cement". Figure 4 The hydration heat curve of the cement slurry with phase change microcapsules prepared in Example 1. The maximum hydration heat temperature of the pure cement slurry (Ref.) without any admixtures is 51.5°C. The cement slurries with 1%, 3% and 5% phase change microcapsules added (corresponding to Figure 4 CET 1% , CET 3% , CET 5%) The maximum hydration heat temperatures are 47°C, 45°C and 43°C respectively. Compared with pure cement paste, they are reduced by 8.7%, 12.6%, and 16.5% respectively. This is because the phase change material absorbs the heat released by the hydration of the cement paste through the melting process. It proves that the phase change microcapsules prepared in Example 1 can successfully adjust the cement hydration exothermic temperature.

[0091] The phase change microcapsules prepared in Example 1 were added to the cement slurry system at 1%, 3% and 5% of the mass of Jiahua G-grade oil well cement. The preparation method of the cement slurry, the preparation method of the compressive strength sample and the test method were referred to the standard GB / T.19139-2012 "Test Methods for Oil Well Cement". Figure 5 The compressive strength data of the phase change microcapsules prepared in Example 1 are shown in the figure. As can be seen from the figure, the addition of microcapsules at different addition amounts improves the early compressive strength of cement, and the compressive strength of pure cement 3d is 22.14MPa. The compressive strengths of cement stone containing 1%, 3% and 5% phase change microcapsules after curing for 3 days are 22.59MPa, 22.92MPa and 23.09MPa, respectively, indicating that the phase change microcapsules have the effect of improving the early compressive strength of cement stone. The increase in the compressive strength of cement stone is due to the hydroxyl groups in the epoxy resin improving the dispersibility of cement particles. Hydroxyl groups and other polar groups adsorb on cement particles, resulting in electrostatic repulsion of particles and reducing particle agglomeration. The distribution of cement particles is more uniform, and the gaps between particles are reduced, thereby increasing the compressive strength of cement stone. Secondly, compared with large micron-sized particles, nano-sized particles are more easily dispersed in cement slurry, avoiding the reduction of compressive strength of cement stone due to the generation of large pores.

[0092] The high thermal conductivity nano-scale phase change microcapsules of the present invention have heat regulation capabilities, can effectively reduce the heat of cement hydration, improve the early compressive strength of cement paste, and ensure cementing safety. The high thermal conductivity nano-scale phase change microcapsules have a phase change material as a core and an epoxy resin as a shell. The epoxy resin is wrapped around the phase change material through emulsification and in-situ deposition methods to form a phase change microcapsule, thereby avoiding leakage of the phase change material during use. The phase change material can reduce the hydration heat temperature by absorbing the heat released by cement hydration. The hydroxyl groups on the surface of the epoxy resin promote the uniform dispersion of cement particles, improve the compactness of the cement paste, and further improve the compressive strength of the cement paste. The high thermal conductivity nano-scale phase change microcapsules have the characteristics of simple preparation process, wide source of raw materials, easy practical engineering application, regulating the heat release of cement slurry hydration, and improving the compressive strength of cement paste.

[0093] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing high thermal conductivity nanoscale phase change microcapsules, characterized in that: The following steps are involved: A silane coupling agent is used to perform hydrophobic treatment on the high thermal conductivity nanomaterial to obtain a hydrophobic high thermal conductivity nanomaterial; Mixing the phase change material, epoxy resin and curing agent to obtain an oil phase solution; Adding the hydrophobized high thermal conductivity nanomaterial to the oil phase solution and mixing well to obtain an oil phase mixture; dissolving a cationic emulsifier and a nonionic emulsifier in water to obtain an aqueous solution; adding the oil phase mixture to the aqueous solution under stirring conditions to obtain an emulsion; The emulsion is reacted and then centrifuged to obtain a solid; the solid is freeze-dried to obtain the high thermal conductivity nano-scale phase change microcapsule.

2. The method for preparing high thermal conductivity nanoscale phase change microcapsules according to claim 1, characterized in that: The silane coupling agent is vinyl triethoxysilane, vinyl trimethoxysilane or octadecyl trimethoxysilane; the high thermal conductivity nanomaterial is boron nitride; the mass ratio of the silane coupling agent to the high thermal conductivity nanomaterial is (1-2):1; the hydrophobic treatment is specifically adding the high thermal conductivity nanomaterial to a silane coupling agent solution and reacting at 60-80° C. for 4-6 hours; the solvent of the silane coupling agent solution is acetic acid aqueous solution; and the pH of the silane coupling agent solution is 2-6.

3. The method for preparing high thermal conductivity nanoscale phase change microcapsules according to claim 1, characterized in that: The phase change material is methyl stearate or ethyl stearate; the epoxy resin is epoxy resin E-51, epoxy resin CYDH-3000 or epoxy resin NP170; the curing agent is 4,4′-diaminodicyclohexylmethane or 3,3'-diethyl-4,4'-diaminodiphenylmethane; the mass ratio of the phase change material to the epoxy resin is (2-3):1; the mass ratio of the epoxy resin to the curing agent is 1:0.

3.

4. The method for preparing high thermal conductivity nanoscale phase change microcapsules according to claim 1, characterized in that: The mass ratio of the oil phase solution to the hydrophobized high thermal conductivity nanomaterial is (8.5-10):(0.09-0.3).

5. The method for preparing high thermal conductivity nanoscale phase change microcapsules according to claim 1, characterized in that: The cationic emulsifier is dodecyltrimethylammonium bromide or dodecyltrimethylammonium chloride; the nonionic emulsifier is dodecylphenol polyoxyethylene ether, sorbitan fatty acid ester or polysorbate-20; the concentration of the cationic emulsifier in the aqueous solution is 0.13-0.15 g / mL; the concentration of the nonionic emulsifier in the aqueous solution is 0.4-0.45 g / mL.

6. The method for preparing high thermal conductivity nanoscale phase change microcapsules according to claim 1, characterized in that: The mass volume ratio of the oil phase mixture to the aqueous solution is (9-11) g:100 mL; the stirring condition is: stirring at a speed of 8000-12000 r / min for 8-10 min.

7. The method for preparing high thermal conductivity nanoscale phase change microcapsules according to claim 1, characterized in that: The reaction temperature is 80-100°C and the reaction time is 4-6h.

8. High thermal conductivity nanoscale phase change microcapsules prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the high thermal conductivity nano-scale phase change microcapsule as claimed in claim 8 in cement.

10. The use according to claim 9, characterized in that: The amount of the high thermal conductivity nano-scale phase change microcapsules added to cement is 1-5% of the mass of the cement.

Citation Information

Patent Citations

  • Preparing method for phase transited stored energy microcapsule covered with an organic polymer material

    CN101530772A

  • Anti-icing coating containing alkane phase change microcapsules and its preparation method

    CN102268222A

  • Preparation method of organic-inorganic composite capsule wall energy-storage microcapsule

    CN103769021A

  • Superhydrophobic phase change energy storage material microcapsule and preparation method thereof

    CN109499499A

  • Preparation method of polyurea microcapsule coated with phase change material

    CN109794209A

Cited By

  • Preparation method, product and application of chemical crosslinking hybrid shell phase change microcapsule

    CN120961070A